Neuroprotective and Neurorestorative Effects of Holothuria scabra Extract in the MPTP/MPP+-Induced Mouse and Cellular Models of Parkinson’s Disease - Noonong, Kunwadee; Sobhon, Prasert; Sroyraya, Morakot; Chaithirayanon, Kulathida (Frontiers in Neuroscience, 2020)
Extracts from Holothuria scabra (HS) have been shown to possess anti-inflammation, anti-oxidation, anti-cancer activities, and most recently it was shown to have neuroprotective potential in Caenorhabditis elegans PD model. Here, we assessed whether HS has neuroprotective and neurorestorative effects on dopaminergic neurons in both mouse and cellular models of PD. We found that both pre-treatment and post-treatment with HS improved motor deficits in PD mouse model induced with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) as determined by grid walk test. This was likely mediated by HS protective and restorative effects on maintaining the numbers of dopaminergic neurons and fibers in both substantia nigra pars compacta (SNpc) and striatum. In cellular model of PD, HS significantly attenuated 1-methyl-4-phenylpyridinium (MPP+)-induced apoptosis of DAergic-like neurons differentiated from SH-SY5Y cells by enhancing the expression of Bcl-2, suppressing the expression of Cleaved-Caspase 3 and preventing depolarization of mitochondrial membrane. In addition, HS could stimulate the expression of tyrosine hydroxylase (TH) and suppressed the formation of α-synuclein protein. Taken together, our in vivo and in vitro findings suggested that HS is an attractive candidate for the neuroprotection rather than neurorestoration in PD.